What is known about severe and very severe chronic fatigue syndrome? A scoping review. Issue 3 (3rd July 2017) - Strassheim, Victoria; Lambson, Rebecca; Hackett, Katie L.; Newton, Julia L.
ABSTRACT: Background: Chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) affects 0.4% of the population. It is characterised by disabling fatigue and a combination of self-reported symptoms which include impairments in concentration, short-term memory, sleep disturbances, post-exertional malaise and musculoskeletal pain. There are four categories of severity in the CFS/ME population: mild; moderate; severe; and very severe which are expanded on elsewhere and adopted by the National Institute for Health and Care Excellence [NICE. Chronic fatigue syndrome/myalgic encephelomyelitis diagnosis and management in adults and children; 2007]. Objective: Identify research relating to those severely and very severely affected by CFS/ME. Methods: We searched electronic databases for relevant studies using pre-defined search terms: 'chronic fatigue syndrome' and 'sever' which covers 'severe' and 'severely'. Included were English language papers published in full that discretely identified severely and very severely affected CFS/ME populations from the broader CFS/ME population. Results: Over 2000 papers were reviewed and 21 papers met the selection criteria. The capture produced both adult and paediatric populations with a variety of methodologies. Wide differences in illness characterisation, definition and measurement were found. Case studies reported that in extreme presentations very severe CFS/ME individuals may be confined to bed, requiring reduced light and noise exposure. Conclusion: This review highlights the limited research focusing on the severely affected CFS/ME population. The heterogeneity of the condition contributes to the lack of consensus concerning definitive diagnostic criteria and functional measures to assess disability. Focused research to understand the disease characteristics of the most severely ill will help to advance our understanding of possible phenotypes associated with distinct severity categories.